Student Experiences Engaging in Interdisciplinary Research Collaborations: A Case Study for Social Work Education. (2nd October 2019) - Miller, Vivian J.; Murphy, Erin R.; Cronley, Courtney; Fields, Noelle L.; Keaton, Craig
ABSTRACT: This article provides a case study of student experiences working as part of an interdisciplinary research team. A team of graduate-level students from social work, civil engineering, and computer science collaborated on the design of a mobile device application that captures data regarding how transportation disadvantage affects the lived experiences of community-dwelling older adults and single parents experiencing homelessness with dependent children. An online survey (N=5) was used to assess student experiences on the team. Findings from this case study have important implications for engaging students in interdisciplinary applied research, including challenging them to expand their knowledge base beyond the traditional confines of their disciplines, encouraging critical and creative thinking skills, and harnessing technology for the greater social good.